Spatial and temporal variations of the subtidal meiobenthic community of the central coast of Venezuela - Pereira, Carlos (2020)
Meiobenthos is a sediment-dwelling community with various taxonomic groups ranging in size from 63 to 500 µm. As a matter and energy link between primary producers and macrofauna, they have other functions in the ecosystem. Since this group has been scarcely studied in Venezuela, it was proposed to analyze the spatial and temporal variations in the composition and abundance of subtidal meiobenthos in the country's central coast. Samplings were conducted monthly from June 2014 to March 2015. In each sampling campaign, 12 random stations were established, and three samples were taken at each using a cylindrical sampler of 5.0 cm internal diameter. Organisms were identified and counted using microscopes, and data was processed using hypothesis tests (ANOSIM) and multivariate analyzes (SIMPER, nMDS). Meiobenthos showed a richness of 164 morphotypes and 14 phyla, with a dominance of planktonic copepods and foraminifers, followed by cnidarians and mollusks. Out of the total species reported, 84 are strictly benthic. Regarding abundance, there was a greater representation of foraminifera, followed by nematodes and mollusks, with values higher than those reported for tropical areas. Spatially, no differences were found in the composition and abundance of this community. However, two maximums were found throughout the study period, one starting in June until reaching maximum densities between August and October and the second one in February